The Main Goals and Objectives of Teaching Foreign Languages (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
At present, teaching English is an increasingly relevant and integral part of teaching children in elementary school. This is justified by the fact that the age characteristics of children of elementary school age are considered the most favorable for the start of education. The first years of schooling are important in preparing a child for adulthood.